Enhancement and Optimization Mechanisms of Biogas Production for Rural Household Energy in Developing Countries: A review - Yitayal Addis Alemayehu (Center of Biomass & Renewable Energy (CBIORE), 2015)
Anaerobic digestion is common but vital process used for biogas and fertilizer production as well as one method for waste treatment. The process is currently used in developing countries primarily for biogas production in the household level of rural people. The aim of this review is to indicate possible ways of including rural households who own less than four heads of cattle for the biogas programs in developing countries. The review provides different research out puts on using biogas substrates other than cow dung or its mix through different enhancement and optimization mechanisms. Many biodegradable materials have been studied for alternative methane production. Therefore, these substrates could be used for production by addressing the optimum conditions for each factor and each processes for enhanced and optimized biogas production.